Public Policy Strategies in Addressing Poverty and Social Inequality in Indonesia - Lestari, Nisa; Alam, Nabil; Yusfiani Ginova, Ade; Pratama, Inka Nusamuda (Visi Pencerah Nusantara, 2025)
This study aims to identify, evaluate, and formulate effective public policy strategies to address poverty and social inequality in Indonesia simultaneously, in an integrated manner, and with a focus on sustainable development. Using a qualitative approach with the Systematic Literature Review (SLR) method, this study analyzes various relevant research results from the Dimensions and Scopus databases for the period 2020–2025. Inclusion criteria include reputable scientific articles that explicitly discuss public policy strategies related to poverty and inequality in Indonesia. The findings indicate that existing policies are still partial, not integrated across sectors and regions, and lack responsiveness to a multidimensional approach to poverty. This study emphasizes the importance of integrating adaptive social protection, utilizing longitudinal data, and learning from international practices, particularly rural revitalization in China, to support the transformation of social interventions at the local level. The proposed strategic recommendations include strengthening the implementation of the Village Law, inclusive agrarian reform, and integrating SDGs principles into national policies. This research contributes to closing the conceptual and practical gaps regarding the effectiveness of evidence-based social policies in reducing poverty and structural inequality in Indonesia.